La influencia de la minería de texto de la web, de opinión pública y hechos en la difusión de la información para la sociedad: evaluación comparativa - Marin Santos, Senny Priscila (2020)
With the evolution of technology, the ways of communicating and transmitting information have revolutionized, every day and every moment information of all kinds is generated in which the management of this, documentation and knowledge is routed as a strategic mechanism of first order. In the present case study, we intend to analyze the influence of web text mining, public opinion and facts in the dissemination of information for society, for which a non-experimental design of qualitative approach oriented to the study is used of the behavior of the intervening variables, using methods such as the inductive and deductive of descriptive and explanatory types with techniques such as the interview for the collection of the information applied to the netizens who use the web for various activities, which have shown that mining of Text can be dangerous if it is not used properly and of great value by making it useful for its various benefits.